2013
DOI: 10.1016/j.intell.2012.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Problems in deriving Italian regional differences in intelligence from 2009 PISA data

Abstract: Recent results of international assessment programs (e.g., PISA) have shown a large difference in high school students' performance between northern and southern Italy. On this basis, it has been argued that the discrepancy reflects differences in average intelligence of the inhabitants of regions and is associated with genetic factors (Lynn, 2010a;. This paper provides evidence in contrast to this conclusion by arguing that the use of PISA data to make inferences about regional differences in intelligence is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 38 publications
2
10
0
1
Order By: Relevance
“…These changes may be explained only by environmentally factors, including improvements in educational resources and policies, and, almost certainly, not by enhancement in nutrition (as pointed out in Section 3). Given the magnitude of variations, the comparative performances of the Northern and the Southern areas may not, furthermore, be explained by differences in the shares of immigrant students, even though their share is higher in Northern Italy (Cornoldi et al, 2013). Notably, these trends are consistent to those observed at the international level for IQs (Flynn, 2012), for scholastic achievement tests (Meisenberg & Woodley, 2013), and for regional IQs (Roivainen, 2012).…”
Section: International and Regional Differences In Test Scoresmentioning
confidence: 65%
See 1 more Smart Citation
“…These changes may be explained only by environmentally factors, including improvements in educational resources and policies, and, almost certainly, not by enhancement in nutrition (as pointed out in Section 3). Given the magnitude of variations, the comparative performances of the Northern and the Southern areas may not, furthermore, be explained by differences in the shares of immigrant students, even though their share is higher in Northern Italy (Cornoldi et al, 2013). Notably, these trends are consistent to those observed at the international level for IQs (Flynn, 2012), for scholastic achievement tests (Meisenberg & Woodley, 2013), and for regional IQs (Roivainen, 2012).…”
Section: International and Regional Differences In Test Scoresmentioning
confidence: 65%
“…Some scholars reacted critically to Lynn, both on methodological and historical grounds (Beraldo, 2010;Cornoldi, Giofrè, & Martini, 2013;Cornoldi, Belacchi, Giofrè, Martini, & Tressoldi, 2010;D'Amico, Cardaci, Di Nuovo, & Naglieri, 2012;Daniele & Malanima, 2011a;Felice & Giugliano, 2011;Robinson, Saggino, & Tommasi, 2011). In replying to his critics, Lynn (2010bLynn ( , 2012a provided further evidence of a North-South IQ gap of about 10 points, and showed that Italian regional IQ differences are related to the frequencies of genetic markers for the percentages of North African ancestry in the Southern populations.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…Lynn (2010) used data from the 2006 PISA tests, which were available for only 12 Italian regions, while Lynn (2012b) used data from the 2009 PISA tests. Because Lynn's data (2010Lynn's data ( , 2012b have been subjected to a number of criticisms (Beraldo, 2010;Felice & Giugliano, 2011;Cornoldi, Giofre, & Martini, 2013; but see Piffer & Lynn, 2014), I check the robustness of my results for Italy against an alternative dataset that was compiled by Templer (2012) from a nationwide IQ survey 3 ; to my knowledge, no alternative dataset exists for Spain. Encouragingly, the Pearson correlation between Templer's (2012) measure of intelligence and the measure calculated from the 2009 and 2012 PISA tests is very high, namely r = .88 (p b 0.001).…”
Section: Data For Spanish and Italian Regionsmentioning
confidence: 99%
“…INVALSI, an Italian institution, uses larger samples which additionally include children. The northern intellectual advantage is less dramatic in INVALSI scores than in PISA scores (Cornoldi et al, 2010;Cornoldi, Giofré & Martini, 2013) or is not seen at all in the first years of school (Daniele & Malanima, 2011;Robinson, Saggino & Tommasi, 2011). On the other hand, significant latitude-IQ-GDP correlations have emerged in the Raven standardization in Italy (Cornoldi et al, 2010) -objected by D'Amico et al (2012) -and in other tests (e.g., Piffer & Lynn, 2014).…”
mentioning
confidence: 94%